2019
DOI: 10.1371/journal.pone.0212292
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis infection among patients attending sexual and reproductive health clinics: A cross-sectional study in Bao'an District, Shenzhen, China

Abstract: This study aimed to estimate the prevalence of chlamydial trachomatis (CT) infection and explore its risk factors among patients attending sexual and reproductive health clinics in Shenzhen, China. We collected demographic and clinical information from attendees (aged 18–49). CT and Neisseria gonorrhoeae (NG) infection was determined by nucleic acid amplification test (NAAT) on self-collected urine specimens. Of 1,938 participants recruited, 10.3% (95% confidence interval [CI]: 9.6%-11.0%) tested positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
(60 reference statements)
3
8
1
Order By: Relevance
“…According to the multivariate analysis, marital status and registered residence were not significantly associated with CT infection, but being single, divorced, or widowed and registered residence of other provinces were potential risk factors of CT infection in the univariate analysis. Consistent with our findings, a study in Shenzhen reported that single, divorced, or widowed and migrant women were more likely to have unprotected sexual behavior, and thus more likely to infect CT [13] …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the multivariate analysis, marital status and registered residence were not significantly associated with CT infection, but being single, divorced, or widowed and registered residence of other provinces were potential risk factors of CT infection in the univariate analysis. Consistent with our findings, a study in Shenzhen reported that single, divorced, or widowed and migrant women were more likely to have unprotected sexual behavior, and thus more likely to infect CT [13] …”
Section: Discussionsupporting
confidence: 91%
“…We observed a CT prevalence of more than 16%, with higher prevalence among STD clinic patients and lower prevalence among gynecology clinic patients. Our observed prevalence was significantly higher than that reported in Shenzhen (5.4% in 2012), [7] Shaanxi (3.4%), [9] and Beijing (2.2%), [10] and higher than that in Shenzhen (10.3% in 2018) [13] . This difference might be associated with the admittance criteria of our study participants as we required that eligible participants had urinary or genital tract symptoms.…”
Section: Discussioncontrasting
confidence: 56%
“…A nationwide scheme called the National Chlamydia Screening Programme (NCSP) was put forward in the UK [ 10 ], and all sexually active men and women aged under 25 years were targeted for annual chlamydia screening through various clinical and nonclinical settings. Similarly, the Shenzhen Gonorrhea and Chlamydia Intervention Programme (SGCIP), a pilot project of a national programme in China (the China Chlamydia Intervention Programme), was launched in 2017, and it was the first city-level CT screening programme in China [ 11 ]. However, there are no policy strategies for routine CT screening in China.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, adults aged 25 years or older should not be neglected in CT screening in China. A study in China reported a high prevalence (9.09%) of CT infection among hospital-based patients aged > 25 years [ 11 ]. It is known that CT screening in the population with CT prevalence > 3% is cost-effective [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) indicated a substantial global burden of CT infections in 2016, with the pooled prevalence of 3.8% in women and about 124.3 million cases of CT worldwide in women and men aged 15-49 years of age [1]. Previous studies in China also showed a large burden of CT infections, with a prevalence of 4.1% among women [2] and a higher prevalence (10.1%) among female patients attending sexual and reproductive health clinics [3]. Untreated CT infection in women is associated with several serious sequelae including pelvic inflammatory disease, ectopic pregnancy, chronic pelvic pain, and tubal factor infertility [4].…”
Section: Introductionmentioning
confidence: 99%